2017 IEEE International Conference on Communications (ICC) 2017
DOI: 10.1109/icc.2017.7997220
|View full text |Cite
|
Sign up to set email alerts
|

Popularity evolution of professional users on facebook

Abstract: Popularity in social media is an important objective for professional users (e.g. companies, celebrities, and public figures, etc). A simple yet prominent metric utilized to measure the popularity of a user is the number of fans or followers she succeed to attract to her page. Popularity is influenced by several factors which identifying them is an interesting research topic. This paper aims to understand this phenomenon in social media by exploring the popularity evolution for professional users in Facebook.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…This sample was derived from a total of the 120 most popular brands’ pages in Greece, for that period of time, that resulted to a total of 83 active pages during the time of our research (Table I). The popularity of the pages was determined by the number of fans-subscribers (likes) (Qualman, 2010) in July 2016, as provided and categorized by Socialbakers (2017), following the relevant literature that has used data from this source to identify brands page popularity (Luarn et al , 2015; Chua and Banerjee, 2015b; Mohammadi et al , 2017), and included only brand pages that are in Greek.…”
Section: Methodsmentioning
confidence: 99%
“…This sample was derived from a total of the 120 most popular brands’ pages in Greece, for that period of time, that resulted to a total of 83 active pages during the time of our research (Table I). The popularity of the pages was determined by the number of fans-subscribers (likes) (Qualman, 2010) in July 2016, as provided and categorized by Socialbakers (2017), following the relevant literature that has used data from this source to identify brands page popularity (Luarn et al , 2015; Chua and Banerjee, 2015b; Mohammadi et al , 2017), and included only brand pages that are in Greek.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, online users’ sense of self-worth, well-being, and social capital is derived from their connections and centrality in these online communities (Ellison et al, 2007; Steinfield et al, 2008; Wilcox & Stephen, 2013). Moreover, as in any social group, users strive for more status and popularity among their online peers by pursuing greater numbers of friends, likes, followers, comments, retweets, and so on (Mohammadi et al, 2017; Scissors et al, 2016). Having lower numbers of these metrics is associated with lower self-worth and well-being—findings consistent with extant work on lower social rank or status (Zell & Moeller, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Mariam Adedoyin-Olowe et al [18] provided a survey of data mining and data analysis techniques for Social Media Analysis much of the work is done in this dimension R. Farahbakhsh et al [6] crawled 479K random user profiles on Facebook and studied the sensitivity of various attributes and listed few which are rarely disclosed by users and are considered private. In another study, S. Mohammadi et al [7] www.ijacsa.thesai.org explored the popularity evolution for professional users in Facebook. They monitored 8K most popular professional users on Facebook over a period of 14 months and concluded that being active and famous correlate positively with the popularity trend.…”
Section: Similar Work In Data Analysismentioning
confidence: 99%